### Home > CALC > Chapter 6 > Lesson 6.3.2 > Problem 6-92

6-92.

Consider the relation

*y*^{3}− 3*y*=*x*^{3}+ 1. Homework Help ✎Find

in terms of *x*and*y*.Find

Find all points where the derivative is undefined.

You could simplify now, if you choose.

has both *x* and *y* variables.

So, before you evaluate, use the original equation

(*y*^{3} − 3*y* = *x*^{3} + 1) to find the *y*-value that corresponds with *x* = 0. It is possible that there will be more than one.

*y*^{3} − 3*y* = (0)^{3} + 1*y*^{3} − 3*y* − 1 = 0

Use a calculator to find the THREE *y*-values that correspond with *x* = 0.